Perancangan Dan Analisis Struktur Mekanik Prototipe Mesin CNC Milling 3-Axis - Devri Naldy; Syafri Syafri; Mustafa Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Computer Numerically Controlled (CNC) Machine is a machine tool equipped with mechanical systems and computer-based controls that capable to read the instruction code such as N, G, F, T, etc. These codes will be instructed to CNC machine interface system, so that the machine can work in accordance with the listing program that has been created. In general, the selling price of the machine is expensive. Therefore, in this study a low cost CNC machine has been designed for small and medium enterprises (UKM). Design stage consist of a needs analysis, preparation of the technical specifications of the product, design concept of the product to find alternative concept product and choose the concept product. From design concept to be developed do static analysis on mechanical components CNC machines that include stress and deformation due to loading and its own weight. Static analysis is conducted in two ways, with manual calculations and finite element analysis using software Autodesk Inventor 2012 Student Edition. Results of static analysis shows that stress occurs at 7.122 MPa on the z-axis, 72.31 MPa on the y-axis and 2,202 MPa on the x-axis. Deformation is equal to 0.003644 mm on the z-axis, 0.5404 mm on the y-axis and 0.005173 mm on the x-axis.Keyword : CNC Machine, Autodesk Inventor, stress, deformation